2002
DOI: 10.1210/jcem.87.8.8756
|View full text |Cite
|
Sign up to set email alerts
|

Expression of PAX8-PPARγ1 Rearrangements in Both Follicular Thyroid Carcinomas and Adenomas

Abstract: Recently, a translocation t(2;3)(q13;p25), leading to the formation of a chimeric PAX8-peroxisome proliferator-activated receptor (PPAR)gamma 1 oncogene, was detected in follicular thyroid carcinomas (FTC), but not in follicular thyroid adenomas (FTA), papillary thyroid carcinomas (PTC), or multinodular hyperplasias. However, previous cytogenetic studies have identified the t(2;3)(q13;p25) translocation also in some cases of FTA. In this study, we have combined RT-PCR with primers in exons 4-8 of PAX8 and in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
38
2
4

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(44 citation statements)
references
References 13 publications
0
38
2
4
Order By: Relevance
“…Chromosomal translocations involving PAX3, PAX5, PAX7 or PAX8 genes in alveolar rhabdomyosarcoma, B-lymphoid malignancies, or thyroid cancer, respectively, suggest that PAX genes have an oncogenic capacity when constitutively expressed, either as part of a fusion gene, or as a whole gene (Barr et al, 1993;Davis et al, 1994;Morrison et al, 1998a;Kroll et al, 2000;Cazzaniga et al, 2001;Marques et al, 2002). In addition, PAX genes are persistently expressed in several embryonal tumors (Dressler and Douglass, 1992;Eccles et al, 1992Eccles et al, , 1995Bernasconi et al, 1996) and adult tumors (Fabbro et al, 1994;Gnarra and Dressler, 1995;Stuart et al, 1995b;Scholl et al, 2001;Silberstein et al, 2002), and reduced survival has been observed in rhabdomyosarcoma or melanoma cell lines following treatment with PAX3 antisense oligonucleotides (Bernasconi et al, 1996;Scholl et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Chromosomal translocations involving PAX3, PAX5, PAX7 or PAX8 genes in alveolar rhabdomyosarcoma, B-lymphoid malignancies, or thyroid cancer, respectively, suggest that PAX genes have an oncogenic capacity when constitutively expressed, either as part of a fusion gene, or as a whole gene (Barr et al, 1993;Davis et al, 1994;Morrison et al, 1998a;Kroll et al, 2000;Cazzaniga et al, 2001;Marques et al, 2002). In addition, PAX genes are persistently expressed in several embryonal tumors (Dressler and Douglass, 1992;Eccles et al, 1992Eccles et al, , 1995Bernasconi et al, 1996) and adult tumors (Fabbro et al, 1994;Gnarra and Dressler, 1995;Stuart et al, 1995b;Scholl et al, 2001;Silberstein et al, 2002), and reduced survival has been observed in rhabdomyosarcoma or melanoma cell lines following treatment with PAX3 antisense oligonucleotides (Bernasconi et al, 1996;Scholl et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…PAX8-PPARg rearrangements have been demonstrated in FTCs and follicular adenomas, but not in other types of thyroid tumors or hyperplastic nodules Marques et al, 2002;Nikiforova et al, 2002Nikiforova et al, , 2003Cheung et al, 2003;Dwight et al, 2003). Screening of large tumor series has identified PAX8-PPARg in 29-62% of FTCs and much less frequently in adenomas.…”
Section: Introductionmentioning
confidence: 99%
“…Rearrangements involving PAX-8 and PPARg were reported by Kroll et al (2000) as specific for FTC (63% of the cases). More recently, PAX8/PPARg was detected by RT-PCR in 25-56% of FTC and in 0-13% of follicular adenomas (Marques et al, 2002;Nikiforova et al, 2002). Mutations of one of the three RAS genes have been reported in 18-52% of FTC and in 24-53% of follicular adenomas (Nikiforova et al, 2002).…”
mentioning
confidence: 99%